¿La crisis del transporte...? - López Abuin, Alberto J. (1961)
The transportation problem in Argentina is erroneously set: its signs have been inverted. The transportation capacity existing in the country is more than sufficient for the needs of the national economy. The only economic solution is its better utilization and requires only progressive and partial investments. One must avoid unnecessary duplications of expenses, imports and investment, which should be reserved for sectors showing a deficit and underdeveloped areas for lack of alternative means. The transportation system should be integrated and adequate to the country's social and economic structure; it must serve its development, supply the needs, redistribute and level wealth and income. Its contributive regulations and tariffs should assist these aims. There is an urgent necessity for a complete reconsideration and an integral and scientific reset of the problem, as everybody is aware of the superficially and incoherence of criterion formulated without statistical support.